A Case Study on the Use of Auditory Integration Training as a Treatment for Stereotypy. (17th June 2015) - LaFrance, Danielle L.; Miguel, Caio F.; Donahue, Jacquelyn N.; Fechter, Timothy R.
<x xml:space="preserve">Abstract</x> The purpose of the current study was to assess the effectiveness of auditory integration training (AIT) as a treatment for motor stereotypy. The participant was a 5‐year‐old boy diagnosed with autism who had been prescribed AIT. We used an ABCBCA reversal design to examine the effectiveness of AIT on stereotypy. Data were collected for 5 min before, during, and after each experimental condition. Results showed that AIT did not decrease stereotypy. In fact, the total overall occurrence of stereotypy increased and remained high, suggesting that AIT was not an effective treatment for this participant. Copyright © 2015 John Wiley & Sons, Ltd.